2022
DOI: 10.3389/fnagi.2022.870442
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Traditional Chinese Medicine Constitution and Age-Related Cognitive Decline in Chinese Centenarians

Abstract: BackgroundAge-related cognitive decline (ARCD) is a common condition among older adults, affecting 100 million people worldwide. Traditional Chinese Medicine’s (TCM) constitution is closely related to the occurrence and development of diseases in the elderly population. However, little is known about the relationships between TCM constitution and ARCD in the super-aged population. The present study aimed to investigate the relationships between the TCM constitution and ARCD in Chinese centenarians and to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Yi-Qi-Huo-Xue recipe is a unique prescription for Qi-deficiency and blood stasis ( Wu et al, 2014 ). The relationship between TCM constitution and age-related cognitive decline has been demonstrated in a larger sample of elderly people ( Sun et al, 2022 ). Evidence already exists that TCM constitution is related to emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Yi-Qi-Huo-Xue recipe is a unique prescription for Qi-deficiency and blood stasis ( Wu et al, 2014 ). The relationship between TCM constitution and age-related cognitive decline has been demonstrated in a larger sample of elderly people ( Sun et al, 2022 ). Evidence already exists that TCM constitution is related to emotions.…”
Section: Discussionmentioning
confidence: 99%
“…The study of TCM constitution is the most crucial part of "treating the disease before it happens." Currently, TCM constitution identi cation has been used as one of the methods for screening and preventing diseases in many elds [29]. Tongue image is the most easily observed, collected, and judged index in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies have shown that the activity and expression of c-Abl are significantly increased in the brains of PD patients. Kinase blockers can improve brain function, reduce neuron death, inhibit CDK5 phosphorylation, regulate α-synuclein elimination, and inhibit Parkin phosphorylation [89][90][91][92][93]. In addition to animal experiments, clinical studies have also found that the treatment of patients with moderate or severe PD with nilotinib for 6 months can significantly alleviate cognitive symptoms [94].…”
Section: Roles Of C-abl Blockersmentioning
confidence: 99%